The effect of CagA status on response to Helicobacter pylori eradication therapy - Murat SARUÇ,; Gamze GÖKSEL,; Sabriye ÖZKAYA,; Feyzullah GÜÇLÜ,; Beril ÖZBAKKALOĞLU,; Hakan YÜCEYAR, (Turkish Journal of Gastroenterology, 2019)
-